Perbedaan Pengetahuan Scabies Antara Sebelum dan Sesudah Dilakukan Promosi Kesehatan di Pondok Pesantren Mambaul Kirom Tanjung Raya Kabupaten Mesuji - Okti Feronika; Febria Listina; Nova Mega Rukmana (Malahayati Nursing Journal, 2025)
ABSTRACT Scabies is a parasitic disease of the skin caused by the entry of an organism called Sarcoptes scabiei var homonis belonging to the order Acariformes, family Sarcoptidae, genus Sarcoptes. The aim of this research was to determine the difference in knowledge of scabies between before and after health promotion was carried out at the Mambaul Kirom Tanjung Raya Islamic Boarding School, Mesuji Regency in 2024. This type of quantitative research uses pre-experimental methods and one group pretest posttest research design. The sample in this study consisted of 65 students from the Mambaul Kirom Islamic Boarding School. The statistical test used in this research is the Wilcoxon Signed Rank Test. The research results showed that the average knowledge of students before health promotion was carried out at the Mambaul Kirom Islamic Boarding School was 69.23. with a standard deviation of 15.17, the minimum knowledge is 20 and the maximum is. The average knowledge of students after health promotion at the Mambaul Kirom Islamic Boarding School is 94.05 with a standard deviation of 5.90, the minimum knowledge is 80 and the maximum is 100. There is difference in scabies knowledge between before and after health promotion was carried out at the Mambaul Kirom Tanjung Raya Islamic Boarding School, Mesuji Regency in 2024, with p-value = 0.001. The conclusion of health promotion has a significant influence on the knowledge of students about scabies with the hope that this knowledge can change clean and healthy living behavior so that there is an increase in health levels. The suggestion in this study is to improve education by collaborating with health workers about scabies or related to the importance of health for students at the Mambaul Kirom Islamic boarding school Keywords: Health Prmotion, Scabies   ABSTRAK Scabies adalah penyakit parasit pada kulit yang disebabkan masuknya organisme yaitu bernama sarcoptes scabiei var homonis termasuk ordo acariformes, family sarcoptidae, genus sarcoptes. Tujuan penelitian ini adalah untuk mengetahui perbedaan pengetahuan scabies antara sebelum dan sesudah dilakukan promosi kesehatan di Pondok Pesantren Mambaul Kirom Tanjung Raya Kabupaten Mesuji Tahun 2024. Jenis penelitian kuantitatif dengan metode pra eksperimental serta desain penelitian one group pretest posttest. Sampel pada penelitian ini berjumlah 65 responden santri Ponpes Mambaul Kirom. Uji statistik yang digunakan pada penelitian ini yaitu uji Wilcoxon Signed Rank Test. Hasil penelitian didapatkan rata-rata pengetahuan santri sebelum dilakukan promosi kesehatan di Pondok Pesantren Mambaul Kirom yaitu sebesar 69,23. dengan standar deviasi 15,17, pengetahuan minimal adalah 20 dan maksimal 87. Rata-rata pengetahuan santri sesudah dilakukan promosi kesehatan di Pondok Pesantren Mambaul Kirom yaitu sebesar 94,05 dengan standar deviasi 5,90, pengetahuan minimal adalah 80 dan maksimal 100. Ada perbedaan pengetahuan scabies antara sebelum dan sesudah dilakukan promosi kesehatan di Pondok Pesantren Mambaul Kirom Tanjung Raya Kabupaten Mesuji Tahun 2024, dengan p-value = 0,001. Kesimpulan promosi kesehatan memberikan pengaruh yang signifikan terhadap pengetahuan santri tentang penyakit scabies dengan harapan pengetahuan tersebut dapat merubah prilaku hidup bersih dan sehat sehingga terjadi peningkatan derajat kesehatan. Saran pada penelitian ini yaitu untuk meningkatkan edukasi dengan berkolaborasi dengan pihak tenaga kesehatan tentang scabies atau terkait pentingnya kesehatan unuk para santri di pondok pesantren Mambaul kirom. Kata Kunci: Promosi Kesehatan, Scabies